Pertumbuhan Ekonomi, Korupsi dan Foreign Direct Investment (FDI): Studi pada Lower Middle Income Countries ASEAN - Aulia Irfan; Hasdi Aimon (Universitas Negeri Padang, 2020)
This study intends to look at the causality relationship between economic growth, corruption and foreign direct investment (FDI) in lower middle income countries in ASEAN. This study uses panel data starting from 2009-2018, which consists of 6 countries in ASEAN using the Vector Auto Regression (VPAR) processing method. The results of this study show that: (1) No causal relationship was found between economic growth and corruption in lower middle income countries in ASEAN, but only had a one-way relationship of economic growth against corruption in lower middle income countries in ASEAN, (2) No found a causal relationship between economic growth and foreign direct investment (FDI) in lower middle income countries in ASEAN, both one way and reciprocity, (3) No causal relationship was found between corruption and foreign direct investment (FDI) in lower middle income countries in ASEAN, but has a one-way relationship from corruption to foreign direct investment (FDI) in lower middle income countries in ASEAN